2021
DOI: 10.3389/fonc.2021.630256
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Outcome of Osimertinib Treatment in Lung Adenocarcinoma Patients With Acquired KRAS Mutations

Abstract: BackgroundOsimertinib belongs to the third-generation epidermal growth factor receptor tyrosine kinase inhibitor that has shown positive effects in treating lung adenocarcinoma cancer. However, the subsequent resistance to Osimertinib has become a clinical challenge.Case PresentationWe present two lung adenocarcinoma cases that developed a resistance to Osimertinib. Among them, one patient attained both KRAS exon 2 and exon 3 mutations and was given paclitaxel (albumin-bound) plus carboplatin. The other patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Xiu et al reported a patient with re-biopsy of KRAS G12D and Q61H on osimertinib progression failed to benefit from paclitaxel with carboplatin. In addition, another patient with acquired KRAS R68S responded to nivolumab with chemotherapy [108]. The standard treatment of acquired KRAS mutation after osimertinib still needs more clinical trials to explore.…”
Section: Mapk Signal Pathway Alterationsmentioning
confidence: 99%
“…Xiu et al reported a patient with re-biopsy of KRAS G12D and Q61H on osimertinib progression failed to benefit from paclitaxel with carboplatin. In addition, another patient with acquired KRAS R68S responded to nivolumab with chemotherapy [108]. The standard treatment of acquired KRAS mutation after osimertinib still needs more clinical trials to explore.…”
Section: Mapk Signal Pathway Alterationsmentioning
confidence: 99%
“…In addition, acquired resistance to both irreversible and reversible EGFR-TKIs, including osimertinib and ge tinib, has been reported in NSCLC and lung adenocarcinoma due to EGFR-dependent and EGFRindependent mechanisms. These include mutations in the EGFR kinase domain duplication (EGFR-KDD) (102) or in the EGFR gene (103), mutations in KRAS exon 3 (R68S) (104), and the involvement of hsa_circ_0005576 via miR-512-5p/IGF1R signaling (105). Acquired drug resistance in EGFR-mutant NSCLC patients is a common reason for the limited long-term e cacy of targeted therapy (106).…”
Section: Intrinsic and Acquired Resistance To Rtkis In Different Cancersmentioning
confidence: 99%
“…However, few EGFR-TKI is effective in treating KRAS-mutant NSCLC due to the special resistance ( Pao et al, 2004 ; Kobayashi et al, 2005 ; Linardou et al, 2008 ; Mao et al, 2010 ). In the case reports written by Dr. Xiu’s team, KRAS G12S -mutant NSCLC patients treated with the third-generation EGFR-TKI osimertinib experienced rapid disease progression instead ( Xiu et al, 2021 ). Fortunately, combination treatment with EGFR-TKI and other inhibitors has been found to effectively treat KRAS-mutant NSCLC, as shown in the section below.…”
Section: Direct and Indirect Attempts To Target Kirsten Rat Sarcoma V...mentioning
confidence: 99%